The destruction of SFRY and Serbia - Jovanovic, Vladislav (Napredak, 2021)
The paper recapitulates the process of the destruction of the Yugoslav state (SFRY and FRY). Special attention is given to the key factor in that process, the will of the West, embodied in the USA and the EC (EU), for whom the continued existence of Yugoslavia was no longer of geopolitical interest. The conferences on Yugoslavia, organized in Brussels and the Hague, were supposed to serve to legitimize this goal: the disappearance of Yugoslavia.The author points out that when the West did not manage to achieve its goal with political solutions, it involved NATO, through the aggression in 1999. Previously, Serbia’s legitimate opposition to terrorist acts by the KLA on its territory, as an internal issue par excellence, was declared a threat to „peace and security in the world”, and the UN Security Council took it as a permanent topic of its sessions. There had been secessionist uprisings and armed conflicts in UN member states before, as there are today, but the Security Council never before dared to violate the article of the UN Charter that states that these questions are the exclusive competence of the member state concerned. An exception was made only in the case of Serbia, although the defense against KLA terrorism was legal and limited to the territory of the Autonomous Province of Kosovo and Metohija, i.e., the Yugoslav state border was never crossed. The false claim of William Walker, the head of the OSCE mission in Kosovo and Metohija, concerning the massacre in Racak, was the cause of the war of aggression against the FRY. By illegally naming the protectorate of Kosovo as the so-called state of the Albanian national minority, the West took this as the final stroke in the dismemberment of Yugoslavia and Serbia, thus ignoring the story of the phoenix rising from its ashes.